Exploring The Triad: Unveiling The Relationship Between Job Characteristics, Job Satisfaction, And Employee Performance - Fika Rahmanita; Najmudin Najmudin; Sudarto Sudarto (Cita konsultindo, 2024)
This research was conducted to determine the relationship between job characteristics, job satisfaction and lecturer performance. This research was carried out using a research method based on a quantitative approach which was developed using the causality method and SEM-PLS as a data analysis method. The research results show that there are variables that have a strong relationship to performance, namely job characteristics and job satisfaction. The findings show that job characteristics have a strong relationship with performance and job characteristics have a strong relationship with job satisfaction.